MANAJEMEN PEMBELAJARAN BAHASA ARAB UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI MADRASAH ALIYAH AL-AZIZIYAH PUTRA GUNUNG SARI - IZOMI, M. SYAHRUL (GANEC SWARA, 2024)
The aim of this research is to find out the management of Arabic language learning at Al-aziziyah high school son of Gunung Sari, to find out how students' learning motivation is in learning Arabic at Al-aziziyah high school son of Gunung Sari. The Research Method used is field research with a qualitative approach whose research (field research) is qualitative, therefore the journal that the author compiled uses a qualitative descriptive approach. Based on the results of the study, it shows that the management of Arabic language learning in Madrasah Aliyah Al-aziziyah putra Gunung sari is not optimal. Student learning motivation in Arabic language learning at Al-aziziyah high school  putra Gunung sari and have not been motivated in learning Arabic even though thoroughly, judging from the learning process of students in the classroom students listen to the teacher who is explaining in front of the class, there is still less motivation to learn Arabic for students in the Al-aziziyah high school putra Gunung sari.